Examining the representation of landscape and its emotional value in German-Swiss fiction between 1840 and 1940 - Giulia Grisot; Berenike Herrmann (Journal of Cultural Analytics)
This paper presents a quantitative analysis of the representation and affective encoding of fictional space in a corpus of 125 Swiss literary prose texts of the 19th and early 20th Century written in German, offering a contribution to both spatial and affective literary studies.